Mucosal-Associated Invariant T (MAIT) Cells Are Impaired in Th17 Associated Primary and Secondary Immunodeficiencies. - Yifang Gao; William Rae; Keseva Ananth Ramakrishnan; Gabriela Barcenas-Morales; Rainer Döffinger; Efrem Eren; Saul N Faust; Christian H Ottensmeier; Anthony P Williams (PLoS ONE)
The recently described Mucosal Associated Invariant T (MAIT) cells mediate specific recognition of bacterial and fungal vitamin B2 metabolites. As innate T cells, they possess broad effector responses, including IFN- including Iproduction, that are comparable to conventional T cell responses. Immunodeficiencies associated with systemic Th17 deficiency may also be compounded by defects in MAIT immunity. We evaluated Th17 immunity in this innate T cell compartment in primary (AD-HIES) and secondary immunodeficiency (thymoma) patients with conventional Th17 deficiency and susceptibility to fungal and bacterial disease. Our results suggest that MAIT cells are both reduced and functional deficient in STAT3 deficiency and thymoma patients with IL-12/23 autoantibodies. In contrast, thymoma patients without autoantibodies preserved the normal number and functional MAIT cells.